Copper‐Based Plasmonic Catalysis: Recent Advances and Future Perspectives. Issue 32 (29th May 2021) - Xin, Yue; Yu, Kaifu; Zhang, Lantian; Yang, Yanru; Yuan, Haibo; Li, Hongliang; Wang, Liangbing; Zeng, Jie
Abstract: With the capability of inducing intense electromagnetic field, energetic charge carriers, and photothermal effect, plasmonic metals provide a unique opportunity for efficient light utilization and chemical transformation. Earth‐abundant low‐cost Cu possesses intense and tunable localized surface plasmon resonance from ultraviolet‐visible to near infrared region. Moreover, Cu essentially exhibits remarkable catalytic performance toward various reactions owing to its intriguing physical and chemical properties. Coupling with light‐harvesting ability and catalytic function, plasmonic Cu serves as a promising platform for efficient light‐driven chemical reaction. Herein, recent advancements of Cu‐based plasmonic photocatalysis are systematically summarized, including designing and synthetic strategies for Cu‐based catalysts, plasmonic catalytic performance, and mechanistic understanding over Cu‐based plasmonic catalysts. What's more, approaches for the enhancement of light utilization efficiency and construction of active centers on Cu‐based plasmonic catalysts are highlighted and discussed in detail, such as morphology and size control, regulation of electronic structure, defect and strain engineering, etc. Remaining challenges and future perspectives for further development of Cu‐based plasmonic catalysis are also proposed. Abstract : Coupling light‐harvesting ability and catalytic function, plasmonic Cu serves as a promising platform for photocatalysis. Recent advancements of Cu‐based plasmonic photocatalysis are systematically summarized, including their design and synthetic strategies, photocatalytic performance, and mechanistic understanding. In addition, approaches for the enhancement of light‐utilization efficiency and construction of active centers on Cu‐based plasmonic catalysts are highlighted and discussed.